2012
DOI: 10.1186/1472-6831-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride bioavailability in saliva and plaque

Abstract: BackgroundDifferent fluoride formulations may have different effects on caries prevention. It was the aim of this clinical study to assess the fluoride content, provided by NaF compared to amine fluoride, in saliva and plaque.MethodsEight trained volunteers brushed their teeth in the morning for 3 minutes with either NaF or amine fluoride, and saliva and 3-day-plaque-regrowth was collected at 5 time intervals during 6 hours after tooth brushing. The amount of collected saliva and plaque was measured, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
11
27
0
Order By: Relevance
“…26 However, in Naumova et al's study they did not observe any difference between these two types of fluoride combinations. 36 In the current study, all the subjects used toothpaste containing Na 2 PO 3 F and the results have shown its effectiveness.…”
Section: B) the Effect Of The Sequence Of Toothbrushing And Flossing mentioning
confidence: 59%
See 2 more Smart Citations
“…26 However, in Naumova et al's study they did not observe any difference between these two types of fluoride combinations. 36 In the current study, all the subjects used toothpaste containing Na 2 PO 3 F and the results have shown its effectiveness.…”
Section: B) the Effect Of The Sequence Of Toothbrushing And Flossing mentioning
confidence: 59%
“…36,37 For example, while using NaF solution for 30 minutes, fluoride reaches deep into the plaque and this means that even in thick biofilm plaque (more than 1 mm), if given sufficient time, fluoride penetration into the deeper layers of plaque is possible. The studies have shown that the general concentration of plaque fluoride and penetration of fluoride inside the plaque depends on the contact duration with fluoride.…”
Section: B) the Effect Of The Sequence Of Toothbrushing And Flossing mentioning
confidence: 99%
See 1 more Smart Citation
“…Collins and Dawes [1] calculated the total area of the oral cavity to determine the thickness of the salivary film covering the oral mucosa. The salivary film is an important reservoir for fluoride [11], and it is needed to moisten the oral cavity; it varies in thickness depending on the total surface area, salivary secretion rate and composition [1,3,5]. However, previous studies did not take into account the total size of the tongue, which is enlarged by its numerous papillae.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of publications about whole saliva content deal with supernatant saliva. Some studies have shown that AmF binds to plaque32 and reduces the viability of plaque bacteria33. There are no data about the weight and the fluoride distribution between the two fractions of whole saliva under different psychological conditions in healthy people.…”
Section: Discussionmentioning
confidence: 99%